Scientific Practicum for Students of the Specialty «Medical Biophysics» - A. M. Chernysh; D. S. Belopakhov; A. A. Belyaevskaya; A. V. Zakaryan; M. S. Kupriyanova; M. A. Postnikov; E. V. Sergeenko; I. M. Shogenov (Общая реаниматология, 2016)
This article focuses on specialized scientific Practicum organized on April 14s 2016 by the Laboratory of biophysics of cells membranes in critical illness of V. A. Negovsky Research Institute of General Reanimatology for students enrolled in the specialty «Medical Biophysics» at the I. M. Sechenov First Moscow State Medical University. During the study students had mastered a number of techniques: atomic force microscopy, calibrated electroporation, spectrophotometry. Students familiarized with the methodology of scientific experiment and mathematical treatment of the results.